Optimizing the tax risk of profit tax through tax control - Yangieva Nargiza Saidkulovna (Euro Asian Journal Publishing, 2025)
This article is devoted to the analysis of the issues of optimizing tax risk for profit tax through tax control.
Keywords: tax risk; tax control; tax risks